Changes of competitive performance, training load and tethered force during tapering in young swimmers - Drosou, E.; Toubekis, A.; Gourgoulis, V.; Thomaidis, S.; Douda, H.1; Tokmakidis, S. P. (Biomechanics and Medicine in Swimming XI, 2010)
During a four-week training period closing with a two-week taper before a National competition (NC) the training load (TL) of twelve young swimmers (age: 14.2±1.3 yrs) was calculated by the product of the session-RPE score with the training duration. Tethered swimming force (TF), hand-grip strength (HG) and body fat (BF) evaluated 34, 20 and 6 days before the NC were unchanged (p>0.05). The TL difference of week 4 vs. week 1 before the NC was related to percent performance change (0.11±1.6%, p>0.05; r=0.63, p<0.05). The TF, HG and BF changes were not related to performance changes (p>0.05). The TL changes alone accounted for 40% (r2=0.4, SEE=1.37%, p<0.05) of the variation of percentage performance changes. The session-RPE training load calculation may be useful for effective taper planning.